Transport-bound mobility and settlement structures in the context of the sustainable spatial development of metropolitan regions - H. Motzkus, Arnd (Raumforschung und Raumordnung | Spatial Research and Planning, 2001)
In the context of the striving to achieve sustainable transport and settlement development, a heated debate is currently taking place both within spatial planning circles and in spatial research on the manner and extent to which such models for settlement structure as the currently preferred paradigm of polycentric concentration might be capable of suppressing future traffic growth, without however unduly restricting the freedom of people to participate in the life of society or the exchange of goods and services. Taking as its point of departure current trends in settlement structure in the areas around metropolitan centres, and focusing on their significance for the structure and efficiency of functional linkages, this article looks in quite concrete terms into ways of fleshing out the settlement-structure strategy which envisages a region of “short distances”, and characterised by unusually low levels of private car use, in order to render it capable of contributing towards achieving a sustainable pattern of mobility in metropolitan regions.
Keywords: Article